A Study on the Current Status and Countermeasures of Foreign Language Education in Higher Vocational Colleges Supporting the Local Cultural Tourism Industry Development—Taking Nanchong Vocational College of Culture and Tourism as an Example - Xu, Benchuan (Journal of Educational Research and Policies, 2025)
This paper takes Nanchong Vocational College of Culture and Tourism as an example and conducts an in-depth analysis of the current status of its foreign language education in serving the cultural tourism industry of Langzhong Ancient City. The research reveals several issues: the curriculum settings are disconnected from the actual needs of the local cultural tourism industry, and the textbooks lack local characteristics; practical teaching is confined to on-campus simulations and lacks integration with real cultural tourism scenarios; the faculty lacks a professional background in the cultural tourism industry and international experience; school-enterprise cooperation is relatively single in form and lacks a long-term and stable mechanism; and students have limited opportunities to participate in practical activities and lack an understanding of the actual needs of the local cultural tourism industry. In response to these problems, this paper proposes countermeasures and suggestions such as optimizing curriculum settings and developing teaching materials, strengthening practical teaching, enhancing faculty development, deepening school-enterprise cooperation, and motivating student participation. These measures can effectively improve the quality and relevance of vocational foreign language education, cultivate high-quality foreign language talents for the local cultural tourism industry, promote the deep integration and coordinated development of vocational foreign language education and the cultural tourism industry, and provide strong support for local economic growth.